Evaluation of intracellular cytokines in covid-19 vaccinated individuals - Yahcob, Ofelia (2022)
Coronavirus disease 2019 (COVID-19) has infected over 500 million people and has caused 6 million deaths worldwide. Many studies have reported that the “cytokine storm” is associated with poor outcomes and severe complications in this infection. COVID-19 vaccine should be suppressed cytokine storm at least hamper its deleterious impact by stimulation of the immune system. This study is important to provide preliminary data on the intracellular cytokines among vaccinated individual for the future study related to COVID-19 vaccination. The study aimed to determine the level of IL-2, IL-4, IFN-γ and TNF-α in COVID-19 vaccinated individuals as well as expression of surface antigens CD3/CD4, CD3/CD8. In this study, peripheral mononuclear blood cell (PBMC) was stimulated using PepTivator SAR-CoV-2 Pot S1 peptide. Stimulated PBMC were stained, and cells were acquired by a flow cytometer. The results showed that IL-2, IL-4, IFN-γ and TNF-α were secreted by CD4+ and CD8+ in all individuals following vaccination. In this study, these intracellular cytokines were consistently produced after second dose and booster vaccination. In conclusion, the sample size in this study is small and does not represent the entire population. As a result, more research is needed to determine the level of IL-2, IL-4, IFN-γ and TNF- α expression on CD4+ or CD8+ T cells after vaccination and their role in the prevention of cytokine storm in COVID-19 infections and protection against infection.